Sistem Monitoring Security Berbasis Website dan Aplikasi Android Menggunakan Metode Agile pada Universitas Mathla’ul Anwar Banten - Bagas Agung nugraha; Zaenal Hakim; Ervi NUrafliyan susanti (SITUSTIKA FIKUNMA, 2024)
The problem is that it is difficult for officials of institutions or sections that deal with security to monitor security activities on guard because the habit of not patrolling to monitor the situation is often carried out by security on guard and security changes are difficult to supervise. The purpose of this study is to create a security monitoring system to make it easier for officials of institutions or security departments to monitor security patrol activities in a repetitive period from the start of patrol activities and also security change activities so that the delivery of all activities carried out in the form of data is also expected to improve the quality of security work. The method used in this study is the Agile method, this method was chosen because it can help system makers in making a system more efficiently and in accordance with the needs of the place of application of the system. The result of this study is a security monitoring system that can monitor security activities from patrol activities to security change activities, with this monitoring system can help officials of institutions or sections that take care of security to be able to monitor security activities from patrol activities to security change activities on guard.